دراسة عمليات الاطماء في بحيرة سد 16 تشرين - حسن, عزالدين; حماد, منذر; حماد, مفيدة; بوبو, معن; يازجي, ظافر (Latakia University Journal -Engineering Sciences Series, 2019)
This research aims to estimate the amount of water erosion in the basin of the Northern Alkabeer Al Shimali River, and the percentage of it, that reaches to a reservoir of the 16 November dam, and how these sediments distribute in the reservoir and to suggest appropriate solutions to reduce the amounts of these sediments. This study included calculating the basin characteristics of the Northern Alkabeer Al Shimali River by splitting it into sub-basins using the (GIS and WMS 7.1 software), as well as calculating the total amount of sediments, which results from water erosion in the study area using the general equation of soil loss (USLE). The study found that the annual amount of total sediments which deposited in the lake were . And the amount of sediments collected in the lake during the investment period (31 years), was (14160986 ton), that equivalent to 12103407 C.M. These results corresponded to 97,743% with the survey which conducted by researchers team, and finished in June 2017. The survey result showed that, the total loss of reservoir storage volumes during the investment period is equivalent to 12,382,930 C.M. Which leads to a decrease in storage capacity of reservoir by 6.2%, that require finding appropriate solutions to reduce this quantity and mitigate their negative impact. يهدف البحث إلى تقدير كمية الانجراف المائي للتربة في حوض نهر الكبير الشمالي ونسبة ما يصل منها الى بحيرة سد 16 تشرين, وكيفية توزع هذه الرواسب في البحيرة، واقتراح الحلول المناسبة للتقليل من كميات هذه الرواسب. تضمنت هذه الدراسة استنتاج خواص الحوض الساكب لنهر الكبير الشمالي عبر تجزئته الى أحواض فرعية باستخدام برنامج نمذجة المياه السطحية ((WMS 7.1 وبرنامج GIS, و حساب الكمية الإجمالية للرواسب الناتجة من الانجراف المائي للتربة في منطقة البحث باستخدام المعادلة العامة لفقد التربة . توصلت الدراسة إلى أن كمية الرواسب الاجمالية السنوية التي تترسب في بحيرة سد 16 تشرين تبلغ , و بلغت كمية الرواسب التي تجمعت في البحيرة خلال مدة الاستثمار 31 سنة ، أي ما يعادل ، وتطابقت هذه النتائج بنسبة 97,75 % مع نتائج أعمال المسح التي قام بها فريق الباحثين، التي انتهت في حزيران 2017 ، حيث بينت أن مجموع الحجوم التخزينية التي فقدتها البحيرة خلال مدة الاستثمار بلغت 12,382,930 C.M. الأمر الذي يؤدي إلى تناقص الطاقة التخزينية لبحيرة السد بمعدل 6,2%, وهذا يستدعي إيجاد الحلول المناسبة من أجل التقليل ,من هذه الكمية والتخفيف من تأثيرها السلبي.